Abstract algebra : applications to Galois theory, algebraic geometry, representation theory and cryptography - Carstensen, Celine; Fine, Benjamin, 1948-; Moldenhauer, Anja; Rosenberger, Gerhard (De Gruyter, 2019)
A new approach to conveying abstract algebra, the area that studies algebraic structures, such as groups, rings, fields, modules, vector spaces, and algebras, that is essential to various scientific disciplines such as particle physics and cryptology. It provides a well written account of the theoretical foundations and it also includes a chapter on cryptography. End of chapter problems help readers with accessing the subjects.- Resumé vydavatel
Edition statement from cover.
Keywords: algebra; Galoisova teorie; algebraická geometrie; kryptografie; Galois theory; algebraic geometry; cryptography; elektronické knihy; monografie; electronic books; monographs